Typology of Houses for Fishermen Disaster Response to Fishermen’s Settlements in the Rangas Distrrict of Majene, West Sulawesi - Sutriani Shafa (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2019)
The high annual percentage of the population has an impact on the level of population density. The increase in population affects the level of need for shelter that creates new settlement groups. The need for each year has increased with the creation of residential space groups that have made coastal space areas so fast that sometimes ignoring the aspects of security, protection and government regulations that only want space to be able to build a house as a place where they live. The study of the problem in this study is how the typology of houses that are responsive to disasters in the fishing settlement space in Rangas, Majene Regency, West Sulawesi with the approach to the use of space in relation to the typology of the house and the factors that influence. The method used is descriptive qualitative by classifying home typology groups based on a matrix grouping by analyzing factors that are considered influential. The results of this study will be seen by comparing the various typologies of the original form of the fishermen's house and the process of its formation in the settlement space pattern by looking at the effect factors. Then determine several houses that are responsive and prone to disasters. Recommended recommendations from this research will result in proposals for the shape and model of disaster-responsive fishing houses with structural specifications, material use, and appropriate spatial placement in the Fisherman Settlements in Rangas, Majene Regency